2014
DOI: 10.3892/ijo.2014.2711
|View full text |Cite
|
Sign up to set email alerts
|

Selective anticancer effects and protection from chemotherapy by the botanical compound LCS101: Implications for cancer treatment

Abstract: There is a need for new options for reducing the side effects of cancer treatment, without compromising efficacy, enabling patients to complete treatment regimens. The botanical compound LCS101 exhibits inhibitory effects on cancer cell growth, and reduces chemotherapy-induced hematological toxicities. The aim of the present study is to examine the selectivity of the effects of the compound, alone and in conjunction with conventional chemotherapy agents, on cancer cell proliferation. The effects of LCS101 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…A number of the individual LCS101 components have been shown in earlier research to exhibit anticancer activity, at least in the in vitro setting. 25 The first of the studies examining the formula as a whole product examined the cytotoxic effects of LCS101 on human breast cancer cell lines (MDA-231, MDA-453, and T47D), using an XTT viability assay. A nearly 50% growth inhibition was observed in LCS101-treated cells, with a FACS (fluorescence-activated cell sorting) analysis indicating elevated sub-G1 population in treated cells ( P < .05), suggesting that an apoptotic mechanism was responsible for cell death.…”
Section: Selective Anticancer Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of the individual LCS101 components have been shown in earlier research to exhibit anticancer activity, at least in the in vitro setting. 25 The first of the studies examining the formula as a whole product examined the cytotoxic effects of LCS101 on human breast cancer cell lines (MDA-231, MDA-453, and T47D), using an XTT viability assay. A nearly 50% growth inhibition was observed in LCS101-treated cells, with a FACS (fluorescence-activated cell sorting) analysis indicating elevated sub-G1 population in treated cells ( P < .05), suggesting that an apoptotic mechanism was responsible for cell death.…”
Section: Selective Anticancer Effectsmentioning
confidence: 99%
“…Further analysis identified 6 of the 14 LCS101 components as being the most cytotoxic to cancer cells: Ligustrum lucidum, Spatholobus suberectus, Paeonia lactiflora white, Paeonia lactiflora red, Prunella vulgaris , and Scutellaria barbata . 25 It was later shown that these 6 botanicals induce reactive oxygen species in their cytotoxic activity. 27 …”
Section: Selective Anticancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The products studied were chosen in accordance with the principles of traditional Chinese medicine herbology, as well as findings from our previous studies (6). The botanicals that exhibited clear anticancer activity were then tested against the same panel of cells, this time using the ROS scavenger pyruvate.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that apoptosis is critical for the cytotoxicity induced by anticancer drugs (19). Over the years, accumulating evidence has clearly indicated that anticancer drugs are able to induce apoptosis, and that this process is involved in the mediation of their cytotoxic effects (20). In addition, the selective regulation of the apoptotic pathway in cancer cells has been the goal of cancer researchers (21).…”
Section: Introductionmentioning
confidence: 99%